Sit-tight leadership and elections in the SADC. Are elections a credible measure of democracy? - OBEDIAH DODO (African Journal of Governance and Development, 2016)
This analysis explores standard features for democracy juxtaposing with what has been presented by some sit-tight leaders in the Southern African Democratic Community (SADC). It also investigates why elections have failed to pass a credibility test of measuring democracy outside of other features. The analysis guided by the Democratic Theory by Jean Jacques Rousseau argues that in ideal democracy, elections are supposed to help facilitate rotation in leadership in a manner that fosters peace, unity and development. The study argues that there are two countries where the leaders have manipulated the systems so 17 African Journal of Governance and Development | Vol 5 No 2 • December 2016much that democracy ceases to influence political systems. The analysis also argues that most of the challenges experienced in the region harks back to the systems and structure of theregion, which is characterised by fissures, poverty, greed, autocracy and an archaic mentality. Countries in the region need to be frank with each other and get hard on deviants and transgressors.